Legal Implications of Overlapping Property Rights Certificates (Case Study of State Administrative Decision Number: 83/G/2023/PTUN.SMG) - Ajeng Wulandari, Cynthia; Arifulloh, Achmad (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2025)
Overlapping land title certificates is a common problem in the Indonesian land system. Overlapping certificates arise when more than one certificate is issued for the same plot of land due to administrative errors or inconsistencies in physical and legal data. This problem indicates legal uncertainty regarding land ownership. This study aims to analyze the legal implications of overlapping land title certificates based on Decision Number 83/G/2023/PTUN.SMG. The research method used is a descriptive analytical legal case study approach. This approach is used to analyze in depth a case that has permanent legal force, namely Decision Number 83/G/2023/PTUN.SMG, to see how judges apply legal norms, interpret related provisions, and consider legal facts in resolving disputes over overlapping land title certificates. The theories used in this study are the theory of legal certainty and the theory of legal evidence. The results of this study indicate that the problem of overlapping land title certificates is still widespread in Indonesia. This situation raises doubts about the validity of ownership and often leads to legal disputes. Therefore, strengthening the land registration system, improving the accuracy of the land database, and harmonizing regulations and administrative oversight are necessary to ensure optimal legal certainty and protection of land rights.